Dynamics of Islamic Journalistic Communication Digital Era in Indonesia - M. Yoserizal Saragih (Khazanah : Journal of Islamic Studies, 2022)
The aims of study are to find out the dynamics of Islamic journalistic communication digital era in Indonesia. This study used qualitative reseseach method. The result of this study shows that Islamic communication often uses the terms tawashul and ittishal. Tawashul is a process carried out by two parties to exchange information so that the message conveyed can be understood and reaches the two communicating parties. Meanwhile, Ittishal emphasizes the connection aspect of messages, not necessarily two-way communication. In Islamic communication, the message to be conveyed can be through da'wah urging its adherents to spread the message of Islam to all mankind.